Somatostatin and electroacupuncture inhibited c-fos expression in spinal cord of arthritic rats - Ruan Huai-Zhen; Li Xi-Cheng; Li Hai-Di; Zhao Bang-Yun (Acta Pharmacologica Sinica, 2016)
AIM: To observer the effect of intrathecal injection of somatostatin (Som) associated with electroacupuncture (EA) at ""Jiaji"" points on c-fos protein expression of spinal cord in pain rats. METHODS: Rats with adjuvant arthritis were used as pain model and the c-fos-like immunoreactivity (FLI) was detected by immunohistochemistry. RESULTS: The c-fos protein expression induced by arthritis were found in all of the I-X laminae of ipsilateral spinal cord of rats, and most of the labeled cells were located in the laminae I-II and V-VI. Som and EA suppressed the c-fos expression and the lessening of FLI cells in the spinal cord. CONCLUSION: Pathological pain following arthritis activated pain sensitive neurons (PSN) and evoked c-fos expression in spinal cord, Som and EA suppressed activities of these PSN, producing the effect of analgesia.